Assessing Surgical and Medical Complications in Bilateral Abdomen-Based Free Flap Breast Reconstructions Compared With Unilateral Free Flap Breast Reconstructions. Issue 1 (July 2016) - Lin, Ines C.; Nelson, Jonas A.; Wu, Liza C.; Kovach, Stephen J.; Serletti, Joseph M.
Abstract : Background: Prophylactic mastectomy is more common, with many patients seeking reconstruction. Bilateral free flap reconstructions subject patients to 2 flaps and longer operations, potentially increasing their risk for complications. We hypothesized that bilateral abdomen-based free flap reconstruction patients are a unique patient population with a higher rate of perioperative complications. Methods: A retrospective chart review compared all 444 bilateral abdomen-based free flap breast reconstructions (in 222 patients) and 367 unilateral free flap breast reconstructions, performed at a single institution between March 2005 and July 2011. Patient and surgical characteristics and complications were studied. Results: Bilateral reconstruction patients were slightly younger and heavier (mean, 49.2 years and 77.7 kg) and more likely to be white. Bilateral reconstructions were more often immediate reconstructions and less likely to have postoperative radiation therapy. These patients had longer surgical times and higher rates of intraoperative arterial thrombosis, but there were no significant differences in postoperative thrombosis or flap loss rates between the groups. The bilateral reconstruction patients, however, did have higher rates of minor surgical and medical complications, including a higher rate of lower extremity deep venous thrombosis (1.8% vs 0.3%, P = 0.045). Conclusions: We find that bilateral abdomen-based free flap breast reconstruction patients do not have higher rates of major postsurgical complications such as flap loss or postoperative thrombosis. However, higher rates of minor surgical and postoperative medical complications, including significantly more cases of lower extremity deep venous thrombosis, are seen. These findings are important for patient counseling and perioperative management.